Flexural performance of cast-in-place concrete-filled steel tube piles under varying axial load. (May 2022) - Subedi, Naresh; Thusoo, Shreya; Obara, Taku; Kono, Susumu; Kaneko, Osamu; Hayakawa, Tetsuo; Watanabe, Hidekazu; Mukai, Tomohisa
Abstract: Concrete-filled steel tube (CFST) piles with thin-walled tubes are widely used as foundations for buildings and bridges in high seismic regions. To design these piles for large earthquakes, it is necessary to test specimens of realistic size under axial loads representative of actual design conditions. However, previous experimental studies of CFSTs were carried out mostly on small-diameter specimens with small or no axial load. To address this issue, cyclic flexural tests were conducted on five large-scale CFST pile specimens under varying axial load, with the range of axial load ratio (−0.21 to 0.38) and internal reinforcement as test variables. The specimens had a diameter of 1200 mm and diameter-to-thickness ratio of 125. This study discusses issues relevant to the design and performance assessment of piles such as moment capacity, hysteretic response, damage progression, strain distribution, and strain limits. It is observed that the ultimate condition of CFST piles is governed by the rupture of the tube, and these piles retain axial load-carrying capacity even after the tube ruptures. Internal reinforcement is effective to improve the deformation capacity and energy dissipation of piles. These findings contribute towards the rational seismic design of CFST pile foundations for large earthquakes. Highlights: Large-scale tests on concrete-filled steel tube (CFST) piles ( D = 1200  mm, D / t = 125 ). Attention to damage progression and ultimate behavior under varying axial load. Ultimate condition of CFST piles controlled by the rupture of steel tube. CFST piles retain gravity load-carrying capacity even after the ultimate condition. Internal reinforcement is effective to improve the seismic performance of CFST piles.